Molecular heterogeneity of TFE3 activation in renal cell carcinomas - Macher-Göppinger, Stephan; Roth, Wilfried; Wagener, Nina; Hohenfellner, Markus; Penzel, Roland; Schirmacher, Peter; Aulmann, Sebastian (Modern pathology, 2012)
Renal cell carcinomas associated with Xp11.2 translocations have recently been identified as a distinct biological entity. The translocation results in the fusion of the transcription factor TFE3 to one of several different fusion partners including PRCC, PSF, NONO, ASPL or CTLC with consecutive overexpression of the chimeric protein. As the true frequency of these neoplasms as well as the biological properties of TFE3 activation in renal cell carcinomas are largely unknown, we have examined TFE3 expression as well as the underlying genetic alterations in a large, hospital-based series of renal cell carcinomas with long-term follow-up information. Out of a total of 876 tumours, TFE3 translocations were detected in five cases (0.6%). Three additional cases were identified in a second series of cases comprising of renal cell carcinomas developing in patients before the age of 50. However, using immunohistochemistry, 9% of all renal cell carcinomas showed some degree of TFE3 reactivity. Interestingly, these cases were associated with high nuclear grade, greater tumour extent and metastatic disease as well as an unfavourable patient outcome on uni- and multivariate analysis. Fluorescence in situ hybridisation (FISH) revealed TFE3 amplifications as an additional, novel mechanism leading to increased TFE3 expression levels. In conclusion, our data show that Xp11 translocation renal cell carcinomas are uncommon tumours accounting for <1% of adult renal cell carcinomas and that the diagnosis of Xp11 translocation renal cell carcinomas needs to be verified using molecular techniques. In turn, TFE3 overexpressing tumours show an aggressive behaviour and Xp11 translocation is only one of several possible underlying genomic alterations.
Published online 28 October 2011
Gesehen am 23.07.2018